Implementasi Peraturan Presiden Nomor 125 Tahun 2016 Terhadap Penanganan Pengungsi Luar Negeri di Medan - Reni Yuliandari; Hasdiana Juwita Bintang; T. Riza Zarzani (Journal of Mandalika Literature, 2025)
Refugees from Abroad, hereinafter referred to as Refugees, are foreigners who are in the territory of the Unitary State of the Republic of Indonesia due to a well-founded fear of persecution based on race, ethnicity, religion, nationality, membership in a particular social group, and differing political opinions, and do not wish to seek protection from their country of origin and/or have obtained asylum seeker or refugee status from the United Nations through the United Nations High Commissioner for Refugees in Indonesia.This research aims to understand the forms of legal protection for refugees, the rights and obligations of refugees, and how the implementation of Presidential Regulation Number 125 of 2016 affects the handling of refugees in Medan City using a qualitative descriptive research method. The research results show that the implementation of Presidential Regulation Number 125 of 2016 on the Handling of Foreign Refugees in Medan City is proceeding well according to the existing mechanisms.